Apatinib Inhibits Cell Proliferation and Induces Autophagy in Human Papillary Thyroid Carcinoma via the PI3K/Akt/mTOR Signaling Pathway - Meng, Xiangrui; Wang, Huijuan; Zhao, Jingzhu; Hu, Linfei; Zhi, Jingtai; Wei, Songfeng; Ruan, Xianhui; Hou, Xiukun; Li, Dapeng; Zhang, Jun; Yang, Weiwei; Qian, Biyun; et al. (Frontiers in Oncology, 2020)
Background: Patients with metastatic radioiodine-refractory papillary thyroid carcinoma (PTC) have limited treatment options and a poor prognosis. There is an urgent need to develop new drugs targeting PTC for clinical application. Apatinib, a novel small-molecule tyrosine kinase inhibitor (TKI), is highly selective for vascular endothelial growth factor receptor-2 (VEGFR2) and exhibits antitumor effects in a variety of solid tumors. Although apatinib has been shown to be safe and efficacious in radioiodine-refractory differentiated thyroid cancer, the mechanism underlying its antitumor effect is unclear. In this report, we explored the effects of apatinib on PTC in vitro and in vivo. Methods: VEGFR2 expression levels were evaluated by immunohistochemistry (IHC), qPCR, and western blotting (WB). The effects of apatinib on cell viability, colony formation, and migration in the Transwell assay were assessed in vitro, and its effect on tumor growth rate was assessed in vivo. In addition, the levels of proteins in signaling pathways were determined by WB. Finally, the autophagy level was assessed by WB, immunofluorescence (IF), and transmission electron microscopy. Results: We found that high VEGFR2 expression is associated with tumor size, T stage, and lymph node metastasis in patients with PTC and that apatinib inhibits PTC cell growth, promotes apoptosis, and induces cell cycle arrest through the PI3K/Akt/mTOR signaling pathway. Moreover, apatinib induces autophagy, and pharmacological inhibition of autophagy or small interfering RNA (siRNA)-mediated targeting of autophagy-associated gene 5 (ATG5) can further increase PTC cell apoptosis. Conclusion: Our data suggest that apatinib can induce apoptosis and autophagy via the PI3K/Akt/mTOR signaling pathway for the treatment of PTC and that autophagy is a potential novel target for future therapy in resistant PTC.